Effect of leaching time on phytotoxicity of dissolved organic matter derived from black carbon based on spectroscopy. (15th August 2022) - Zhang, Ruju; Deng, Ze; Li, Jiulong; Zhang, Yunxian; Wei, Zimin; Cao, Huan
Abstract: Black carbon (BC) exports huge amounts of its derived DOM from terrestrial ecosystems annually through a variety of ways (i.e., erosion or runoff migration). The pyrolytic feedstock type and temperature resulted in DOM derived from highly condensed aromatic and non-aromatic BC. However, the behaviors of low aromatic BC-derived DOM at diverse leaching time are poorly understood. In this work, low aromatic BCs were prepared by pyrolysis corn straws at 250 °C, 350 °C and 450 °C. Extraction experiments for four leaching time (6 h, 10 h, 15 h and 21 h) were set up to simulate BC-derived DOM generative process in nature. The phytotoxicity of BC-derived DOM was evaluated via germination index (GI). Spectral characteristics were discussed to analyze the phytotoxicity variations of fluorescence components composition at different time, including the excitation-emission matrix-parallel factor, two-dimensional correlation spectra and Fourier transform infrared spectroscopy. The results suggested that low aromatic BC-derived DOM might contain aromatic phenolic compounds. A longer time contributed to accumulate the complex, hard-to-use organic matters, leading to lower GI. These results would supplement the dynamic spectral characteristics of low aromatic BC-derived DOM and its environmental risks during the leaching process. Graphical abstract: Image 1 Highlights: The dissolved organic matter of black carbon (BC) degraded with the leaching time. BC derived dissolved organic matter (DOM) contained 0.95–5.87 mg/L phenols. Leaching time promoted the dissolution of phenolic compounds from low-aromatic BC. The accumulation of phenolic compounds in BC-derived DOM inhibited root growth.